2021
DOI: 10.1001/jamaophthalmol.2020.5464
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 on Ocular Surfaces in a Cohort of Patients With COVID-19 From the Lombardy Region, Italy

Abstract: 2020, coronavirus disease 2019 (COVID-19) has spread rapidly all over the world, with an epidemiological cluster in Lombardy, Italy. The viral communicability may be mediated by various body fluids, but insufficient information is available on the presence of the virus in human tears. OBJECTIVES To investigate the rate of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in tears collected from patients with COVID-19 by means of real-time reverse transcriptase-polymerase chain reaction (rRT-PCR) ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 66 publications
2
57
0
1
Order By: Relevance
“…SARS-CoV-2 was found on the ocular surface in 52 of 91 patients with COVID-19 (57.1%; 95%CI: 46.3-67.5%) hospitalized in ICU. 18 In the present study, the higher serum levels of neutrophils, C-reactive protein, and D-dimer, laboratorial markers of systemic inflammation, in patients with SARS-CoV-2 detected in tears might suggest higher severity to be associated with a higher percentage of conjunctival positivity. In addition, there was a greater need for mechanical ventilation among these patients.…”
Section: Discussionmentioning
confidence: 44%
“…SARS-CoV-2 was found on the ocular surface in 52 of 91 patients with COVID-19 (57.1%; 95%CI: 46.3-67.5%) hospitalized in ICU. 18 In the present study, the higher serum levels of neutrophils, C-reactive protein, and D-dimer, laboratorial markers of systemic inflammation, in patients with SARS-CoV-2 detected in tears might suggest higher severity to be associated with a higher percentage of conjunctival positivity. In addition, there was a greater need for mechanical ventilation among these patients.…”
Section: Discussionmentioning
confidence: 44%
“…showed that the human cornea does not support SARS-CoV-2 infection despite the expression of ACE2 in the human corneal epithelium 45 . However, studies in COVID-19 patients found an increase of the virus in dry eye disease, suggesting a possible consequence of infection 46 , and in a cohort of patients with COVID-19, 63% had a positive viral test in the conjunctiva, but the origin of the infection was undetermined 47 . Nevertheless, the role of lipid mediators in managing the ACE2 upregulation as well as hyper-inflammation, increase in cytokine expression, and senescence programming after tissue damage uncovers mechanistic insights that are also applicable to other tissues.…”
Section: Discussionmentioning
confidence: 95%
“…The study conducted in Italy (Lombardia) SARS-CoV-2 was found in 57.1% of patients on the ocular surface with a variability of viral load from both eyes [22]. The infectivity of the material was not determined but the results suggested that the test can be positive in conjunctival swab and negative in nasopharingeal swab.…”
Section: Transmissionmentioning
confidence: 98%